The Formation of Chitosan Fiber by Using Different Solution Formulation - Aiman Fazrullillahi, Nur (Progress in Engineering Application and Technology, 2023)
Spinning is one of the methods drawing out fibres or filament from as mass and twisting together to from a yarn in textiles. Nowadays, spinning involves many methods with different technique and equipment. However, the problem arise in this research is the compatibility of the solvent with the base polymer and the coagulation bath during the chemical reaction occur. The main objective of this research is to investigate the formation of chitosan (CTS) fibre by using different solvent of chitosan solution and different coagulation bath. The formulation of the chitosan solution is divided by 8 different testing samples. The experiment is held in UTHM laboratory at block H with fully safety equipment and tools for the setup method of wet spinning process. This study also will enlighten the formulation for the formation of the chitosan fibre with 8 different type of sample that has been prepared whether it works or not. The experiment for the formation of fibre will be conducted with wet spinning method where it is fibre-forming method that involves dissolving the polymer in the solvent and extruding the solution into a chemical bath. The results for all of the 8 testing sample formulation ending with the formation of fibre in 10 seconds and dissolve in the coagulation bath solution.